Challenges and Prospects of Differentiated Learning in Mathematics: Evaluation at Junior High Schools in Bima Regency - Hendrawansyah, Hendrawansyah; Saputra, Adi; Purnama, Purnama; Syarifudin, Syarifudin (Universitas Islam Sultan Agung, 2025)
This study aims to evaluate the implementation of differentiated instruction within the Merdeka Curriculum in mathematics learning at junior high schools in Bima Regency, Indonesia. A qualitative approach was employed, using in-depth interviews with teachers and school principals as the primary data collection technique. The findings reveal that teachers' understanding of differentiated instruction remains varied, with the majority focusing on content differentiation, while process differentiation is still limited, and product differentiation is barely implemented. The main challenges identified include limited instructional time, inadequate facilities, administrative burdens, and insufficient training. Nevertheless, even simple applications of differentiation were found to increase student participation, reduce achievement gaps, and foster learning motivation. These results highlight the positive prospects of differentiated instruction as a strategic approach to improving the quality of mathematics education, provided that teacher capacity is strengthened and supported by school policies as well as contextualized regional education policies. This study contributes to the discourse on inclusive teaching practices and offers recommendations for policy development tailored to local educational needs. Keywords: Differentiated Instruction; Merdeka Curriculum; Mathematics; Inclusive Educatio